Strengthening resistance testing for tuberculosis in India - Investment cost, throughput, and efficiency of new laboratories. (September 2022) - Bashir, Saima; Sarin, Sanjay; Chadha, Sarabjit Singh; Kalra, Aakshi; ThekkePurakkal, Akhil S.; Duraisamy, Karthickeyan; Saacks, Sharon; Gwaza, Gamuchirai P.; Ongarello, Stefano; Denkinger, Claudia M.
Abstract: A lack of laboratory capacity for drug-resistant tuberculosis (DR-TB) testing is a major barrier to DR-TB control. To overcome this barrier, the Central Tuberculosis Division (CTD), Ministry of Health and Family Welfare (MoHFW), Government of India (GoI), and FIND India established a partnership under the National Tuberculosis Elimination Program (NTEP) to strengthen and expand tuberculosis (TB) laboratory diagnostic capabilities. This partnership has led to the establishment of 61 culture & DST laboratories, increasing the testing capacity to a capability of performing over 200, 000 liquid cultures and over 170, 000 molecular drug sensitivity tests annually. In this study, we assess the data on throughput, efficiency, investment cost, and the capacity of the laboratory services supported by this partnership to understand impact and inform future resource allocation. We estimated the technical efficiency using Stochastic Frontier Analysis (SFA). Our results show that the established laboratory network is operating at 69% efficiency, with the capacity to perform an additional 450, 000 cultures and 180, 000 first-line molecular drug-susceptibility tests by 2025. This additional capacity, together with current efforts to enhance the laboratory network, has the potential to make a significant contribution to NTEP's TB elimination target by 2025.